2016
DOI: 10.1111/jnc.13754
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent uptake and trafficking of vesicles capturing extracellular S100B in cultured rat astrocytes

Abstract: Astrocytes, the most heterogeneous glial cells in the central nervous system, contribute to brain homeostasis, by regulating a myriad of functions, including the clearance of extracellular debris. When cells are damaged, cytoplasmic proteins may exit into the extracellular space. One such protein is S100B, which may exert toxic effects on neighboring cells unless it is removed from the extracellular space, but the mechanisms of this clearance are poorly understood. By using time-lapse confocal microscopy and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 83 publications
(120 reference statements)
3
16
1
1
Order By: Relevance
“…Before studying the iPSC-EV-dependent gene regulation of HSCs, we investigated the mechanism of action (MOA) of iPSC-EVs. Our group and others have demonstrated that cell-derived EVs are effectively engulfed by target cells and modulate a variety of cell responses (23)(24)(25)(26). Based on this evidence, we assessed whether this is true for iPSC-EVs as well.…”
Section: Resultsmentioning
confidence: 98%
“…Before studying the iPSC-EV-dependent gene regulation of HSCs, we investigated the mechanism of action (MOA) of iPSC-EVs. Our group and others have demonstrated that cell-derived EVs are effectively engulfed by target cells and modulate a variety of cell responses (23)(24)(25)(26). Based on this evidence, we assessed whether this is true for iPSC-EVs as well.…”
Section: Resultsmentioning
confidence: 98%
“…Data have also been reported indicating that extracellular S100B is captured by vesicles and re‐uptaken by astrocytes in a RAGE‐dependent manner (Lasic et al . ). Interestingly, the activity of S100B has been associated with multimerization, so that tetrameric S100B has been shown to exhibit a higher binding affinity than dimeric S100B to RAGE (Ostendorp et al .…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 97%
“…RAGE is a ubiquitous, transmembrane immunoglobulin-like receptor that binds to a diverse range of extracellular ligands and intracellular effectors, initiating a complex intracellular signaling cascade, which may also be associated with a series of pathological conditions, including neuroinflammatory reaction to neural injury, and concomitantly resulting in an up-regulation of RAGE itself (for review, Bongarzone et al 2017). Data have also been reported indicating that extracellular S100B is captured by vesicles and re-uptaken by astrocytes in a RAGE-dependent manner (Lasic et al 2016). Interestingly, the activity of S100B has been associated with multimerization, so that tetrameric S100B has been shown to exhibit a higher binding affinity than dimeric S100B to RAGE (Ostendorp et al 2005).…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 99%
“…In Schwann cells and glioblastoma, endogenous S100 is localized in vesicle-like structures (Davey et al 2001;Perrone et al 2008) that are translocated across the cell in response to increasing intracellular Ca 2+ or decreasing intracellular Zn 2+ concentration through an endoplasmic reticulum-Golgi-independent pathway (Davey et al 2001) suggesting that it could be released from vesicles. Additional support is provided by the observation that extracellular S100 is recaptured in a time-dependent manner by vesicle endocytosis (Lasič et al 2016). The exact concentration of the protein at the site of release is difficult to estimate, but on the basis of our measurements of S100β-evoked decrease in [Ca 2+ ]e (Fig.…”
Section: Impact Of [Ca 2+ ] E Fluctuations On Cell Signalling Decreamentioning
confidence: 54%